2004
DOI: 10.1093/nar/gkh238
|View full text |Cite
|
Sign up to set email alerts
|

A library of siRNA duplexes targeting the phosphoinositide 3-kinase pathway: determinants of gene silencing for use in cell-based screens

Abstract: Gene silencing through RNA interference (RNAi) has been established as a means of conducting reverse genetic studies. In order to better understand the determinants of short interfering RNA (siRNA) knockdown for use in high-throughput cell-based screens, 148 siRNA duplexes targeting 30 genes within the PI3K pathway were selected and synthesized. The extent of RNA knockdown was measured for 22 genes by quantitative real-time PCR. Analysis of the parameters correlating with effective knockdown showed that (i) du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(128 citation statements)
references
References 25 publications
(13 reference statements)
2
125
1
Order By: Relevance
“…Therefore, the application of PDK1 targeted RNAi to interfere or block the excessively activated P13K/Akt signal transduction pathway has been widely used in gene therapies for many malignant tumors. PDK1 siRNA effectively silences the PDK1 mRNA expression (Hsieh et al, 2004). PKD1 siRNA down-regulates the PDK1 expression specifically in breast cancer MDA-MB-231 cells, and inhibits the cell invasion capacity obviously (Min et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the application of PDK1 targeted RNAi to interfere or block the excessively activated P13K/Akt signal transduction pathway has been widely used in gene therapies for many malignant tumors. PDK1 siRNA effectively silences the PDK1 mRNA expression (Hsieh et al, 2004). PKD1 siRNA down-regulates the PDK1 expression specifically in breast cancer MDA-MB-231 cells, and inhibits the cell invasion capacity obviously (Min et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Small-scale efforts have identified that genome-wide siRNA libraries can be prepared by various methods including chemical synthesis or enzymatic digestion of long dsRNAs. 45,57 Similarly, small-scale proof-of-principle experiments indicated that libraries can be produced by constructing shRNA expression vectors that target each gene. 45,58 Recently, two groups have prepared resources for large-scale RNAi-based screens in mammals.…”
Section: Short Rna-mediated Rnai In Mammalian Cellsmentioning
confidence: 99%
“…We therefore set out to use in situ-synthesized sequences to build shRNA expression libraries targeting nearly every identified and predicted gene in the genomes of several species, including human, mouse and rat. Similar libraries have previously been constructed using conventional oligonucleotides or natural nucleic acids as starting material [28][29][30][31][32][33] . To maximize recovery of accurate clones from our highly structured templates, we used thermostable polymerases that have proofreading capability and are able to effect strand displacement.…”
Section: Accurate Synthesis Of Long Oligonucleotidesmentioning
confidence: 99%